On Third Order Stable Difference Scheme for Hyperbolic Multipoint Nonlocal Boundary Value Problem - Ozgur Yildirim; Meltem Uzun (Discrete Dynamics in Nature and Society)
This paper presents a third order of accuracy stable difference scheme for the approximate solution of multipoint nonlocal boundary value problem of the hyperbolic type in a Hilbert space with self-adjoint positive definite operator. Stability estimates for solution of the difference scheme are obtained. Some results of numerical experiments that support theoretical statements are presented.